Proceedings of the 2020 Federated Conference on Computer Science and Information Systems 2020
DOI: 10.15439/2020f73
|View full text |Cite
|
Sign up to set email alerts
|

An incremental malware detection model for meta-feature API and system call sequence

Abstract: In this technical world, the detection of malware variants is getting cumbersome day by day. Newer variants of malware make it even tougher to detect them. The enormous amount of diversified malware enforced us to stumble on new techniques like machine learning. In this work, we propose an incremental malware detection model for meta-feature API and system call sequence. We represent the host behaviour using a sequence of API calls and system calls. For the creation of sequential system calls, we use NITRSCT (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Moreover, the use of sequential system calls and API call sequences, as demonstrated by [27], enables the incremental detection of malware, addressing the need for continuous monitoring and detection in contemporary cybersecurity. These methods leverage the inherent characteristics of API calls and system calls to detect anomalies and malicious behaviors, aligning with the evolving threat landscape and the need for robust protection against malware, as discussed by [28].…”
Section: Methods Description Limitationsmentioning
confidence: 99%
“…Moreover, the use of sequential system calls and API call sequences, as demonstrated by [27], enables the incremental detection of malware, addressing the need for continuous monitoring and detection in contemporary cybersecurity. These methods leverage the inherent characteristics of API calls and system calls to detect anomalies and malicious behaviors, aligning with the evolving threat landscape and the need for robust protection against malware, as discussed by [28].…”
Section: Methods Description Limitationsmentioning
confidence: 99%
“…Kishore et al. [37] divided the API call sequences into system call sequences and ordinary API call sequences. They identified a bunch of representative features as classification features.…”
Section: Related Workmentioning
confidence: 99%
“…They had demonstrated that their system was efficient, produced accurate results in the presence of noisy data, detected subtle temporal anomalies and minimized false positives, and adaptable to statistical change in the data. Kishore et al [14] proposed an incremental malware detection model for meta-feature API and system call sequence. They used the N-HTM for generating the anomaly score of each element in the sequence of system and API calls.…”
Section: Related State-of-the-art Workmentioning
confidence: 99%